COMPLEX TREATMENT OF COMPLICATED FORMS OF ERYSIPELAS - V.O. Syplyviy; V.V. Dotsenko; D.V. Ievtushenko; O.V. Ievtushenko; O.V. Kolotilov (Сучасні медичні технології)
Summary. Objectives: to analyze the immediate results of the complex treatment of complicated forms of erysipelas.